A novel water borne green textile polyurethane dispersions finishes from cotton (Gossypium arboreum) seed oil based polyol used in modification of cellulosic fabrics - Sidra (Elsevier, 2021)
Now in these days the major challenges in the polymer industry is to evolve sustainable and renewable substitutes to petroleum-based raw resources. Keeping in view of the current challenges a novel series of water-borne polyurethane dispersions were prepared from the renewable resource cottonseed oil-based polyol by varying the polyol contents concerning the 1,4-butanediol. The polyol was prepared by epoxidation and ring-opening procedure and further reacted with the isophorone diisocyanate, dimethylol propionic acid, and 1,4-butanediol to form the final polyurethane dispersions. The FTIR technique was used to confirm the anticipated structure of cotton seed oil-based polyol and final polyurethane dispersions. Different textile tests such as anti-pilling and colorfastness properties were carried out onto the plain weave fabrics of poly/cotton after applying the synthesized dispersions by pad-dry-cure processes. Significant improvement in anti-pilling behavior was shown by the white grade (4), dyed (4), and printed (4/5) fabrics from the untreated fabrics (1/2), (1/2), and (2), respectively. However, colorfastness properties of all the treated fabrics also showed the remarkable enhancement in rating as compared to the untreated fabrics such as colorfastness to rubbing of the dyed fabric improved to grade (3/4) and (4/5) from the untreated fabrics (2) and (3) for wet and dry rubbing. The results revealed that the bio-based polyol in the polyurethane backbone has significantly improved the fabric properties and has applications for better textile performance for polyester/cotton textiles to substitute the petroleum raw material-based finishes.